60S acidic ribosomal protein P1 (RPLP1) is elevated in human endometriotic tissue and in a murine model of endometriosis and is essential for endometriotic epithelial cell survival in vitro. (3rd January 2020) - Alali, Zahraa; Graham, Amanda; Swan, Kimberly; Flyckt, Rebecca; Falcone, Tommaso; Cui, Wei; Yang, Xiaofang; Christianson, Julie; Nothnick, Warren B
Abstract: Endometriosis is a female disease which is defined as the presence of ectopic endometrial tissue and is dependent on estrogen for its survival in these ectopic locations. Expression of the ribosomal protein large P1 (RPLP1) is associated with cell proliferation and invasion in several pathologies, but a role in the pathophysiology of endometriosis has not been explored. In this study, we aimed to evaluate the expression and function of RPLP1 with respect to endometriosis pathophysiology. RPLP1 protein was localised by immunohistochemistry (IHC) in eutopic and ectopic tissue from 28 subjects with confirmed endometriosis and from 20 women without signs or symptoms of the disease, while transcript levels were evaluated by qRT-PCR in 77 endometriotic lesions and 55 matched eutopic endometrial biopsies, and protein expression was evaluated using western blotting in 20 of these matched samples. To evaluate the mechanism for enhanced lesion expression of RPLP1, an experimental murine model of endometriosis was used and RPLP1 expression was localized using IHC. In vitro studies using an endometriosis cell line coupled with shRNA knockdown was used to demonstrate its role in cell survival. Expression of RPLP1 mRNA and protein were significantly higher in ectopic lesion tissue compared to paired eutopic endometrium and immunohistochemical localisation revealed predominant localisation to epithelial cells. This pattern of lesion RPLP1 was recapitulated in mice with experimentally induced endometriosis. Stable knockdown of RPLP1 protein resulted in a significant decrease in cell survival in vitro . These studies reveal that RPLP1 is associated with cell proliferation and/or survival and may play a role in the pathophysiology of endometriosis.